2010
DOI: 10.1111/j.1747-4477.2010.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between sealer penetration and microleakage following the use of MTAD as a final irrigant

Abstract: The relationship between sealer penetration and apical microleakage following the use of MTAD as an irrigant in root canal procedures was evaluated. A collection of 120 human teeth was divided into three groups of 40 in each group. The final rinse was varied as follows: group 1 - the final rinse was saline solution, group 2 - ethylene diamine tetraacetic acid and for group 3 - MTAD. Each group was then divided into two subgroups (20 teeth) and filled with gutta percha and either AH Plus or Dorifill sealer. Hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 22 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…18 There exists literature suggesting that there is no correlation between smear layer, leakage, and bonding strength of the sealers. 19,20,21 Several methods have been used to evaluate the sealing ability of root canal filling materials. 12,17,22 Linear dye microleakage is a commonly used technique to assess leakage in root canals.…”
Section: Discussionmentioning
confidence: 99%
“…18 There exists literature suggesting that there is no correlation between smear layer, leakage, and bonding strength of the sealers. 19,20,21 Several methods have been used to evaluate the sealing ability of root canal filling materials. 12,17,22 Linear dye microleakage is a commonly used technique to assess leakage in root canals.…”
Section: Discussionmentioning
confidence: 99%
“…These materials not only act as antibacterial agents, theoretically speaking, but can also optimize the quality of the seals provided by these penetrations. This hypothesis is based on the concept that tubular dentine cement penetration considerably increases the contact surface of the filling material with the root canal walls, thereby improving the seal 6,19,24 . The possibility of improving the adhesiveness of the filling materials also has the ultimate goal of preventing leakage 13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, these hypotheses have not yet been completely clarified in the literature, and few studies have been performed to investigate these possible correlations 4,6,12,13,19,23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…[1] A few investigators did not observe any significant correlation between degree of micro leakage and sealer penetration into dentinal tubules. [2] But majority of studies suggested that mechanical interlocking of sealer inside dentinal tubules following smear layer removal improve dislocation resistance of root fillings and decrease microleakage. [3][4][5] It was observed that the smear layer obstructed the penetration of sealers into the tubules.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Currently, ethylenediaminetetraacetic acid (EDTA) and sodium hypochlorite (NaOCl) are used to remove the smear layer and improve sealer penetration. [8] Bacteria have been shown to penetrate 150 to 400 μm into dentinal tubules. The ability of the sealers to penetrate into the dentinal tubules may be especially beneficial to control or kill bacteria that may be located there.…”
Section: Introductionmentioning
confidence: 99%